THE HISTORIOGRAPHICAL DISCOURSE OF JUGUN IANFU (Critical Historical Analysis of Historical Biography Momoye Mereka Memanggilku By Eka Hindra and Koichi Kimura): DISKURSUS HISTORIOGRAFI JUGUN IANFU (Analisis Sejarah Kritis Atas Biografi Sejarah Momoye Mereka Memanggilku Karya Eka Hindra dan Koichi Kimura) - Fatma Wati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Momoye, They Call Me is a historical biography of Jugun Ianfu whose entire contents include Mardiyem's acknowledgment as the main character in this book. In 1942-1945 when Japan took over Indonesia from Dutch rule, the Japanese military had forcibly recruited a number of Indonesian women to serve as biological needs for the Japanese military and civilians. This research is intended to explore the dark history of Jugun Ianfu according to Mardiyem's memory construction. Through critical historical tracing, the historical facts of Jugun Ianfu are interpreted in the hope that the Indonesian people, especially the younger generation, can learn about the dark history that befell Indonesian women as a result of the savagery of the Japanese occupation in Indonesia. This textual research can also be interpreted explicitly as a form of criticism of Indonesian historiography which has always marginalized women and silenced historical memories that should be studied by the younger generation of Indonesia. Theoretically, the concept of hermeneutics is very significant in interpreting the meaning of the history of human experience because this concept believes that empirical data shows patterns that give special meaning to human experience. Hermeneutically, Mardiyem's statement in her biography is the most likely textual strategy to provide a different perspective on the dark side of history faced by women during the Japanese occupation in Indonesia.